Silent sinus syndrome: an underdiagnosed entity. (28th August 2015) - Magalhães, Clara; Baptista, Miguel; Lopes, Gustavo; Duarte, Delfim
Abstract : We describe a case of a 33-year-old Caucasian woman with right facial asymmetry and no sinonasal symptoms. She was referred to the ophthalmology department as having right palpebral ptosis. On physical examination, she presented painless enophthalmos and hypoglobus of the right eye. The MRI of the brain only showed sinonasal inflammatory signs of the right maxillary sinus. The CT scan revealed opacification of the right maxillary sinus, with retraction of the sinus walls. We confirmed the diagnosis of silent sinus syndrome. The patient underwent functional endoscopic sinus surgery. One year after surgery, despite clinical and aesthetic improvement, slight enophthalmos remained, but there were no other complications. In our case, the diagnosis of facial asymmetry as ptosis led to an initial imaging investigation to exclude neurological causes. Silent sinus syndrome should be included in the differential diagnosis of facial asymmetry. Despite the clinical suspicion, the diagnosis can only be confirmed by imaging studies.